2021
DOI: 10.1186/s13099-021-00424-6
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasites among intellectually disabled individuals in Iran: a systematic review and meta-analysis

Abstract: Background Poor self-care skills and personal hygiene resulted from limitations in learning and understanding, put intellectually disabled individuals at greater risk for intestinal parasitic infections (IPIs). Despite several regional reports in Iran, the overall burden on IPIs among intellectually disabled individuals is poorly understood. Hence, the present study aimed to estimate the pooled prevalence of IPIs among intellectually disabled individuals in Iran. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…The current study revealed a low prevalence of helminthic parasites compared to protozoan parasites (0.04% and 4.4%, respectively). These results were consistent with the previous studies that indicated a decreasing trend in intestinal helminth infections, while intestinal protozoa still have a high prevalence in various areas of Iran (Rokni 2008 ; Teimouri et al 2020 ; Abbaszadeh Afshar et al 2021 ). The high prevalence of protozoan parasites is possibly due to their high proliferation rate and the simple route of infection via contaminated foods and water (Abera et al 2010 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The current study revealed a low prevalence of helminthic parasites compared to protozoan parasites (0.04% and 4.4%, respectively). These results were consistent with the previous studies that indicated a decreasing trend in intestinal helminth infections, while intestinal protozoa still have a high prevalence in various areas of Iran (Rokni 2008 ; Teimouri et al 2020 ; Abbaszadeh Afshar et al 2021 ). The high prevalence of protozoan parasites is possibly due to their high proliferation rate and the simple route of infection via contaminated foods and water (Abera et al 2010 ).…”
Section: Discussionsupporting
confidence: 93%
“…H. nana , E. vermicularis , and S. stercoralis were reported as the parasitic helminths in the present study. In line with our findings, A. lumbricoides , E. vermicularis , S. stercoralis , and H. nana were the most predominant helminths reported among food handlers and intellectually disabled individuals in Iran (Teimouri et al 2020 ; Abbaszadeh Afshar et al 2021 ). Although the prevalence of human helminthic diseases has decreased in recent decades throughout Iran, some of them, particularly those with direct fecal–oral transmissions, such as Enterobius and Hymenolepis , are still common (Rokni 2008 ; Goudarzi et al 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Blastocystis hominis was the most common detected parasite followed by Entamoeba coli , Giardia lamblia , Cryptosporidium , Iodamoeba butchlii , and Endolimax nana . Blastocystis is considered a common protozoan infection in humans in Iran [ 11 16 ]. Results of a recent systematic review and meta-analysis revealed that Entamoeba coli , Blastocystis spp., and Giardia lamblia are the most prevalent protozoan parasite among intellectually disabled individuals in Iran [ 11 ].…”
Section: Discussionmentioning
confidence: 99%